Saparuik and Moknehi: Kinship-based Tensions in Care for Older People - Jelly, Jelly; Delpada, Benidiktus (Humaniora, 2024)
This article provides information on a comparison of elderly care systems in two regions in Indonesia with different ethnicities and cultures, namely the Minangkabau in West Sumatra and the Abui of Alor. This article shows how the saparuik kinship in the Minangkabau community which is matrilineal with different customary constellations and how the patrilineal moknehi kinship in the Abui community takes care of elderly women. This paper explains the influence of caregivers’ life journey on their burdens of life. The burden of life perceived by caregivers arises from various factors. Among the various influencing factors are emotions, economy, knowledge, kinship and the right to manage inheritance. Kinship is a form of reciprocal relationship between various elements in both Minangkabau and Abui societies. In the Minangkabau ethnic group, the smallest kinship system in society is called saparuik kinship (Minang language), while the smallest kinship system in Abui is called moknehi (Abui language) which means “brother”. Paruik can be interpreted as “stomach”. While the word moknehi, which has variants in Abui such as muknehi, mokneng and motneng, likely derives from words moku “child” and neng “male”, whose meaning is equivalent to “brother, sibling”. Literally, saparuik are people who come from the same stomach or mother, while moknehi refers to people who come from the same mother and or father. People who are in saparuik are people who come from the same grandmother, while moknehi are male brothers who come from the same grandfather, who then develop into several extended families. Both extended families in paruik or moknehi consist of several nuclear families. Likewise, saparuik and moknehi consist of several extended families. The extended family in saparuik is formed in one grandmother (not a literal grandmother, the grandmother in this case is the mother of the grandmother or the grandmother of the grandmother), in one “rumah gadang”, and sharing inheritance. Otherwise, moknehi are not only formed in one grandfather, but also male great-grandfather and great-great-grandfather (male great-grandfather and great-great-grandfather in this case are father of grandfather and grandfather of grandfather), in one clan, and sharing inheritance